The Moderating Role of Financial Development and Taxation in the Relationship Between International Trade and Economic Growth - Ghraieb, Ikram (Journal of Cultural Analysis and Social Change, 2025)
This research explores how financial development and taxation act as moderating factors in the connection between international trade and economic growth in Saudi Arabia, utilizing the Autoregressive Distributed Lag (ARDL) method over the period from 1990 to 2022. International trade is often seen as a crucial driver of economic growth, but its impact is significantly influenced by the country's financial and tax structures. The findings reveal a stable long-term cointegration relationship among these variables. Specifically, international trade positively and significantly contributes to economic growth, with financial development amplifying this effect by improving capital mobilization, investment ability, and risk management. On the other hand, taxation appears to have a detrimental impact on growth, dampening the trade-growth relationship. This suggests that high or distortionary taxes can diminish the benefits derived from trade. The error-correction mechanism indicates a swift adjustment back to long-term equilibrium. These insights highlight the need for synchronized trade, financial, and tax policies to foster sustainable economic growth. The study provides valuable policy recommendations for Saudi Arabia, especially considering its ongoing economic diversification efforts under Vision 2030.